Wives, Widows, and Brides of Christ: Marriage and the Convent in the Historiography of Early Modern Italy - Evangelisti, Silvia (The historical journal, 2000)
Two main alternative paths structured the lives of women in early modern Italy: marriage and the convent. Historians have analysed the disciplinary and economic functions, and the legal, religious and symbolic meaning of these paths, from a variety of perspectives. However, studies of marriage and the convent have mainly developed as two separate fields of historical research. My article reviews these two series of studies in the context of the historiography of early modern Italy, and suggests some of the possible connections between them.